Introduction to ’Grave Matters in Oceania’ - Schoeffel, Penelope; Meleisea, Malama (Waka Kuaka, 2016)
The idea for this collection of articles on burial practices in Pacific Island cultures first came to us in 2013 when we were invited to Sweden to give a lecture on 'an aspect of materiality in Samoa' to the Archaeology Department of the University of Gotland (now the Gotland Campus of Uppsala University). The invitation came from Helene Martinsson-Wallin, Associate Professor of Archaeology there, who had been working with the National University of Samoa for some years to establish the teaching of Archaeology and associated research. As neither of us are archaeologists, our thoughts turned to digging holes in the ground in search of history, and from there to the increasing visibility and variety of graves in Samoa. Thus inspired, we set off with our camera, took pictures of many graves and put together a commentary on what the photographs told us about changing burial practices in Samoa.